Enhanced gas recovery by CO[subscript]2 injection - Sidiq, Hiwa H-Amin (Curtin University, 2010)
The central issue in the physical processes of enhanced gas recovery by carbon dioxide (CO[subscript]2) injection is the extent to which the natural gas will mix with the injected CO[subscript]2 and reduce the calorific value of the natural gas. Mixing in such a system is a diffusion-like process, which definitely depends on the physical properties of the displacing and displaced phases and the heterogeneity of the medium. However CO[subscript]2 undergoes a large change in density in the gas phase as it passes through the critical pressure at temperatures near the critical temperature. At the extreme reservoir conditions with pressure of 6000 psi and temperature of 160 ºC, CO[subscript]2 exhibits a greater viscosity and density when compared to methane. This variation is approximately a factor of three, which is in favour of the CO[subscript]2-natural gas displacement. In contrast, at near supercritical conditions of pressure of 1071 psi and temperature of 31 ºC, the CO[subscript]2 physical properties (viscosity and density) are slightly superior methane’s. Results indicated improved recovery efficiency was obtained with tests that were conducted at higher pore pressure, higher displacement speed and higher methane concentration in the in situ gas. In addition, low quality rock at a lower temperature of 95 ºC also showed better ultimate recovery.In this work, the first ever attempt for measuring interfacial tension (IFT) in a Gas- Gas system, namely supercritical carbon dioxide (SCO[subscript]2) and methane was made. Experiments were conducted at temperatures of 95 °C and 160 °C and pressures from 1000 to 6000 psia, using a modified reverse pendant drop method. It is common knowledge that a thermodynamically stable interface can only exist between two immiscible fluids, nonetheless an “immiscible interface” between two gases (CO[subscript]2- methane) has been observed and is documented within this research work.It was noted that the IFT decreased linearly with both temperature and pressure in the low-pressure range, but was less sensitive at higher pressures. There was a zone in the vicinity of 1500 psia and above that was noted to be independent of temperature where IFT increased sharply. The IFT was almost three times higher at 3000 psia, for the same temperature, compared with 1000 psia. This is attributed to the density of SCO[subscript]2 at 1000 psia being less than 1/3 the density at 3000 psia, at the same temperature.